2019
DOI: 10.1111/geb.13030
|View full text |Cite
|
Sign up to set email alerts
|

Biological controls over the abundances of terrestrial ammonia oxidizers

Abstract: AimAmmonia‐oxidizing archaea (AOA) and bacteria (AOB) are the primary agents for nitrification, converting ammonia (NH4+) into nitrate (NO3−) and modulating plant nitrogen (N) utilization and terrestrial N retention. However, there is still lack of a unifying framework describing the patterns of global AOA and AOB distribution. In particular, biotic interactions are rarely integrated into any of the conceptual models.LocationWorld‐wide.Time period2005–2016.Major taxa studiedAmmonia‐oxidizing archaea and ammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…Our study also revealed that GAN, which uses NH 4 + as a substrate mainly by AOB and AOA (Zhang et al, 2014), is predominantly controlled by C:N (Figure S4), which has a negative correlation with AOA and AOB abundances (Xiao et al, 2021). In soils with high C:N, low N availability is the main limiting factor to AOA and AOB due to strong competition from heterotrophic microbes (Xiao et al, 2020). In the same context, our results emphasized the importance of soil total N in regulating GN, which is in line with findings by Wang et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also revealed that GAN, which uses NH 4 + as a substrate mainly by AOB and AOA (Zhang et al, 2014), is predominantly controlled by C:N (Figure S4), which has a negative correlation with AOA and AOB abundances (Xiao et al, 2021). In soils with high C:N, low N availability is the main limiting factor to AOA and AOB due to strong competition from heterotrophic microbes (Xiao et al, 2020). In the same context, our results emphasized the importance of soil total N in regulating GN, which is in line with findings by Wang et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…The key role of soil ammonia nitrogen in governing both rare and abundant bacterial and fungal community assembly processes might be partially attributed to the functions of nitrogenous nutrients and the physicochemical characteristics of bacteria and fungi (Zhong et al, 2020). Ammonia nitrogen is an important nutrient for plant and microbial growth (Blázquez et al, 2017), and plays an important role in regulating soil nitrogen cycling and nitrogen‐cycling‐related microbial communities (Ma et al, 2020; Xiao et al, 2020). Moreover, ammonia nitrogen is closely correlated with soil bulk density, which in turn affects gas diffusion (e.g., oxygen and carbon dioxide) and microbial activity (Pan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it could be speculated that the plant-dependent reduction of nitrifier populations was due to increased inter-microbial competition between bacterial heterotrophs (stimulated by the plant) and nitrifiers. A possible explanation for the latter theory would be long-term competition for substrate N, proposed to be the predominant control of ammonia oxidizer abundance (Xiao et al 2020). In our experiment, especially the concomitant reduction of amoA and archaeal 16S rRNA gene abundances favors the conceptualized theory of intermicrobial competition (Fig.…”
Section: Inter-microbial Competition Rather Than Bni Determine Aoa and Aob Abundancesmentioning
confidence: 99%